Strategi Kepala Madrasah dalam Mengelola Konflik Antara Guru dan Siswa di MTs Nurul Ihsan NWDI Tanjung Luar: The Principal's Strategy in Managing Conflict between Teachers and Students at MTs. Nurul Ihsan NWDI Tanjung Luar - Sukranudin (Pendidikan Al-Gafari, 2026)
This study aims to explain the strategies of madrasah principals in managing conflicts between teachers and students in the madrasah environment. Conflict between teachers and students is a normal thing and often occurs due to differences in communication and expectations. The research method used is a qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. with the formulation of the problem what are the strategies of madrasah principals in managing internal conflicts and what forms of conflict occur between teachers and students. The subjects of this study were the madrasah principal, the vice principal of student affairs, students, and several subject teachers. The results of the study show that the madrasah principal applies several strategies in managing conflicts, including an open communication approach, mediation between disputing parties, instilling the values ​​of discipline and empathy, and continuous coaching. These strategies have proven effective in creating a conducive madrasah learning atmosphere and strengthening relationships between madrasah residents. This study concludes that the madrasah principal's strategy in resolving existing conflicts is through collaboration, accommodation, and compromise methods. By identifying problems, gathering the parties involved and solving existing problems through mutual deliberation. So that it produces a solution for all parties.